THE ROLE OF INNOVATION CAPABILITY IN ENHANCING SME COMPETITIVE ADVANTAGE: EVIDENCE FROM INDONESIA'S DIGITAL ECONOMY - Bangun Prajadi Cipto Utomo; Tri Djoko Santosa; Ilham Sentosa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The rapid advancement of digital technologies has intensified competition among Small and Medium Enterprises (SMEs), requiring firms to continuously innovate, respond effectively to market changes, and leverage organizational knowledge to sustain competitive advantage. Although previous studies have examined these factors independently, limited research has investigated the integrated effects of open innovation, market orientation, and knowledge management on competitive advantage through innovation capability, particularly in emerging economies. This study examines the direct and indirect relationships among these variables using survey data collected from 200 Indonesian SMEs operating in manufacturing, trade, and service sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that open innovation (β = 0.284), market orientation (β = 0.317), and knowledge management (β = 0.298) positively and significantly influence innovation capability. Furthermore, innovation capability significantly enhances competitive advantage (β = 0.412) and partially mediates the effects of the three antecedent variables. The model explains 68.4% of the variance in innovation capability and 74.1% of the variance in competitive advantage. These findings highlight innovation capability as a strategic mechanism that transforms knowledge resources, external collaboration, and market intelligence into sustainable competitive advantage in an increasingly digital economy.